2007
DOI: 10.1007/s10038-007-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of glutathione S-transferase M1, T1 and P1 in patients with reflux esophagitis and Barrett’s esophagus

Abstract: Reflux esophagitis (RE) and Barrett's esophagus (BE) belong to the most common esophageal complications of gastroesophageal reflux disease. Glutathione S-transferase (GST) enzymes play an important role in cellular protection against oxidative stress and toxic foreign chemicals. Therefore, we investigated the hypothesis that polymorphisms in genes for these detoxifying enzymes could influence susceptibility to RE and BE. GSTM1, GSTT1 and GSTP1 loci were analyzed by PCR-based methods in 64 patients with RE (and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Individuals homozygous for the null allele lack GST enzyme activity and hence may not be able to detoxify the chemicals [29,30]. However, GSTT1 and GSTM1 polymorphisms may not be associated with risk of GERD, though GSTP1 b allele was associated with susceptibility to GERD [31], especially to BE [32].…”
Section: Gst and Risk Of Gerdmentioning
confidence: 80%
“…Individuals homozygous for the null allele lack GST enzyme activity and hence may not be able to detoxify the chemicals [29,30]. However, GSTT1 and GSTM1 polymorphisms may not be associated with risk of GERD, though GSTP1 b allele was associated with susceptibility to GERD [31], especially to BE [32].…”
Section: Gst and Risk Of Gerdmentioning
confidence: 80%
“…Similarly to SCC, it has been postulated that polymorphisms in enzymes involved in the detoxification of xenobiotics and luminal toxic agent might be associated with an increased risk. Four out of five studies reported an increased risk associated with the presence of allelic variant of glutathione-S transferase GSTP1, GSTM1 and GSTT1; the data are however inconclusive [44][45][46][47]; especially since allelic variants from these enzymes were also demonstrated not to have any statistical association with risk [44][45][46][47][48]. As a key regulator of cell cycle progression, cyclin D1 polymorphisms have been investigated in the context of Barrett's carcinogenesis.…”
Section: Adenocarcinomas Of the Oesophagus And Gastro-oesophageal Junmentioning
confidence: 99%
“…Therefore, COMT is a key enzyme for preventing quinone and semiquinone formation via the methylation of hydroxyestrogens [13]. GSTs, SULTs and UGTs inactivate any quinones or semiquinones formed, ultimately lending to their elimination [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%